If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5 = 10 + 4x Reorder the terms: 5 + -2x = 10 + 4x Solving 5 + -2x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + -2x + -4x = 10 + 4x + -4x Combine like terms: -2x + -4x = -6x 5 + -6x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -6x = 10 + 0 5 + -6x = 10 Add '-5' to each side of the equation. 5 + -5 + -6x = 10 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 10 + -5 -6x = 10 + -5 Combine like terms: 10 + -5 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333
| 2x+4=-x-20 | | 22=2y | | 0=x^2+26x+232 | | x+1+2x+2+3x+3+4x=56 | | 2x+7=-x-1 | | 11x-79=47+5x | | 5x-3+2x=2x+2 | | 8=2*b^2 | | (x*x)-5=23 | | 8=2xb^2 | | -4+3x-1=4x+1 | | sin(19x)+sin(7x)=0 | | 64m=cm | | -16n+19=-15n-13 | | c=36(n+16) | | (5x+6y)(5x-6y)=0 | | 8=2(x-2) | | 45=9f | | 5x+6x=-11 | | X^3-3x^2-9x+3=0 | | (4x-5)(3-2x)=12-9(2x-5) | | 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 | | tanx=0.5714 | | 3x+5(6.5)=37 |